Demografické stárnutí v Česku mezi lety 2012–2022 prostřednictvím vybraných retrospektivních a prospektivních ukazatelů - Filip Čábela; Luděk Šídlo (Demografie)
Demographic ageing is considered a significant phenomenon and one of the most important population issues of the 21st century. It is a process that has no parallel in human history but is completely natural. The ageing of the population itself is a consequence of the changing quality of life, a new approach to lifestyle, and improvements in the health status of the population, all of which lead to improvements in the level of mortality, especially at old age. The concept of prospective age is not based on the number of years that a given person has already lived, but on the number of years that people probably have left to live. This paper presents the concept of prospective age and the development of prospective indicators using the example of Czechia between 2012 and 2022, focusing on a comparison of retrospective indicators with prospective ones. The paper also reveals the effect of the Covid-19 pandemic on demographic ageing indicators.